Use of the cloud environment by engineers of the agro-industrial complex - Kriestov, V. (Запоріжжя : 2024, 2024)
EN: becoming more relevant. The use of these technologies in any field of activity is an evolutionary step towards giving the educational process the properties of adaptability, flexibility, openness and mobility. There is an intensive implementation of "cloud technologies" and services in the engineering system of agro-industrial complex workers. The modern new design technology has improved functions for preparing design documentation and allows you to create interactive technical documents and exchange projects on the network. For example, in Solid Edge ST10, it is much easier to optimize the design of parts taking into account the possibilities of additive manufacturing, as well as to request price offers, material options and production times from additive manufacturing service providers. Advanced publishing tools allow you to create interactive technical documentation and share projects in the cloud. These documents always remain linked to the original project data, so the documentation can be quickly updated if the project changes.
Keywords: cloud services; CAD/CAM systems; modeling; calculations; storage